Multiplex PCR detection of mackerel-based food adulteration with pleco and chicken in selected areas around Ciliwung River, Indonesia - RINI WIDAYANTI; HERJUNO ARI NUGROHO; DOROTHEA VERA MEGARANI; DYAH AYU WIDIASIH; SUHENDRA PAKPAHAN (Society for Indonesian Biodiversity, 2023)
Abstract. Widiyanti R, Nugroho HA, Megarani DV, Widiasih DA, Pakpahan S. 2023. Multiplex PCR detection of mackerel-based food adulteration with pleco and chicken in selected areas around Ciliwung River, Indonesia. Biodiversitas 24: 1538-1543. Detecting fish product adulteration is crucial to ensure food safety since pleco meat was already reported to carry several heavy metals that might harm human health. Pleco is invasive species in the Ciliwung River and is commonly used as adulteration material for fish-based products. Adulteration in mackerel-based food products may alter the nutritional value and carry heavy metal contamination from the bottom-feeder fish's meat (pleco). Therefore, using the DNA barcoding technique, a molecular approach has been used to authenticate mackerel fish products (including dumplings and otak-otak). This study aimed to develop a specific multiplex PCR method for simultaneously detecting processed products from mackerel and pleco. The sample consists of 21 processed food items initially made from mackerel. The samples were taken in the selected area around the Ciliwung River. All the samples can be amplified successfully, and amplification lengths were 108, 171, and 300 bp, respectively. Analysis from various claimed mackerel products showed that five samples were positive for pleco adulteration, and 11 products contained chicken meat addition. The phylogenetic tree was constructed from selected sequences from our samples and showed that the amplicons were clustered in three clades, mackerel (Scomberomorus), pleco (Pterygoplichthys), and chicken (Gallus gallusLinnaeus, 1758). The findings of this study revealed that 23.80% (5/21) products contained pleco, and 52.38% (11/21) contained chicken meat addition. The addition of an unusual component to food composition may alter nutritional value as well as may affect food hygiene and safety.